Is the European Charter of Local Self-Government an effective instrument for the protection of local autonomy in Poland? - Zakroczymski, Stanisław (Central European Public Administration Review, 2022)
Purpose: The objective of this research is to examine whether the European Charter of Local Self-Government is, in practice, an effective instrument for the protection of the autonomy of local government in Poland, as well as well as to define the contribution of the Polish case law and administrative practice to the understanding of the principles of the Charter. The importance of the subject is strengthened by the political context. For many years, Poland was considered a model country safeguarding extensive local autonomy. Recently, however, recentralization trends have emerged in government policies.  Design/methodology/approach: The research is based on the qualitative and quantitative empirical research of the case law and administrative practice with elements of doctrinal analysis. Findings: The Charter is present in the case law of the Constitutional Tribunal (22 judgments), administrative courts (166), and public administration bodies supervising local governments (49). The number is high compared to other CoE countries. The administrative courts seem to be more eager to adjudicate in favour of local governments in the cases in which the Charter is referred to. Academic contribution to the field: A specific Polish input to the application of the Charter is the frequent use of the principle of proportionality in the supervision of local governments, which serves the courts as a perfect tool for resolving ‘hard cases’ between the local government and central administration bodies. In several important judgments, Article 11 concerning the judicial protection of local governments was invoked to effectively strike down the law limiting the local governments’ access to court in specific cases. Practical implications: The research may be useful for local government representatives in formulating their litigation strategies, especially in legal disputes with central authorities. Originality/value: This research is the first all-embracing empirical research of the application of the Charter in a country’s legal practice. It shows original ways of the practical use of the Charter not described in the literature so far.
Keywords: administrative courts; European Charter of Local Self-Government; Evropska listina lokalne samouprave; local autonomy; local government; lokalna avtonomija; lokalna samouprava; nadzor nad lokalno samoupravo; supervision of local government; upravna sodišča